EFFICIENCY OF TRANSPULMONARY THERMODILUTION IN THE OPTIMIZATION OF INTENSIVE TREATMENT IN PATIENTS WITH SEVERE NOSOCOMIAL PNEUMONIA - S. N. Avdeykin; I. N. Tyurin; N. A. Karpun (Общая реаниматология, 2015)
Objective: to evaluate the efficiency of transpulmonary thermodilution (TPTD) for the choice of measures to correct hemodynamics in patients with severe nosocomial pneumonia (NP). Subjects and methods. The investigation enrolled 107 NP patients admitted to an intensive care unit (ICU). Group 1 patients were intensively treated in accordance with a protocol for hemodynamic correction during early goaldirected therapy for sepsis. In Group 2, infusion thera py and sympathomimetic agents were prescribed depending on the results of TPTD. Results. Patients in both groups did not differ in the examined clinical and laboratory indicators. On day 1 of intensive therapy, in Group 2 (a TPTD controlled intensive treatment group) the prescription of sympathomimetic drugs was virtually twice more active than in Group 1; and the value of positive hydrobalance was, twice less. In 5 days, the frequency of use of sympathomimetic agents had no intergroup differences and, in 7 days became less in Group 2 patients. After the therapy patients in Group 2 did not require substantial amounts of infusion and great positive hydrobalance, resulting in lower central venous pressure (CVP) values. After 5 days of intensive therapy, the positive hydrobalance in Group 2 patients was 5 times less and on day 7 this indicator became negative. There were no intergroup differences in CVP on day 1; however, this indicator was higher in Group 1 patients from day 2 to the end of the followup period. At days 5—7, Group 2 patients exhibited elevated SvO2 values and hypolactatemia. At day 3, the SOFA severity was somewhat higher in Group 2 than in Group 1, then substantially reduced and on days 5—7 it was 2—2.5 scores lower in Group 2 than in Group 1. The mortality in ICU was 49% and 33% in Groups 1 and 2, respectively (χχ2=3.899; pConclusion. The determination of infusion amounts and indications for the use of sympathomimetic drugs on the basis of the integrated assessment of global enddiastolic volume index, cardiac index, and total peripheral vascular resistance index results in improved clinical outcomes in mechanically ventilated patients with severe NP. This approach ensures the use of sympathomimetic agents and to avoid hypervolemic loading.